Influence of Wellbore Dogleg Severity on Drilling Friction in Horizontal Wells - Shitang Chen; Gui Hu; Xueqin Huang; Guohui Zhang; Xinyun Liu (Geofluids)
In horizontal drilling, high frictional forces adversely influence operation efficiency. The influence of the rate of change in the overall hole trajectory angle (dogleg severity) is often ignored in the prediction of frictional force in drilling program design, and there is a shortage of quantitative analysis. Aiming at this issue, a mathematical model for computing the radial force caused by axial tension, string bending, and gravity of the string was established. It is found that the axial tension and the gravity of the string are the main forces affecting the radial force of the string, and the bending radial force of the medium-long-radius horizontal well is no more than 14% of the gravity of the string. The influence of dogleg severity on the friction in the vertical, building, and horizontal sections was analysed, and the equations for computing the friction were also established. Based on case analysis, it is suggested that dogleg severity should be kept within a lower limit in the vertical section of horizontal wells with a greater TVD (true vertical depth) because the greater the TVD, the higher the add-on factor related to string tension. For example, in the upper well section with a vertical depth of 3000 m, the add-on factor related to string tension is 0.5, and dogleg severity at 1000 m should be controlled within 0.5°/30 m. Lower building rate should be adopted in the early building section, and appropriately higher building rate can be adopted later. Sliding drilling should be practiced as less as possible provided that target hitting is guaranteed, and combined drilling should be used more. In horizontal wells, dogleg severity at certain point of the horizontal section should be controlled inversely proportional to the drilling drag caused by the subsequent points. The closer to target A (the starting point of the horizontal section), the higher the control requirement for dogleg severity, and it can be appropriately reduced in subsequent well section. If the horizontal interval length Lh is 1000 m and the friction coefficient μ is 0.3, then dogleg severity ϑ should be controlled within 1°/30 m at point A and within 2°/30 m at the middle.